What Does It Take for Immigrants to Join Political Parties? - Monika Bozhinoska Lazarova; Thomas Saalfeld; Olaf Seifert (Politics and Governance, 2024)
Political parties are crucial agents in democratic representation and political integration of persons of immigrant origin, a growing category of citizens in the European Union. Research demonstrates that citizens of immigrant origin are less likely to join political parties than persons without a migratory background. Nevertheless, party membership varies across countries and between immigrants. Accounting for such inter-individual and cross-national variations, this article uses secondary data from the European Social Survey, the Migrant Integration Policy Index, and the Varieties of Democracy (V-Dem) project for 25 European democracies to uncover mechanisms that explain the party membership of immigrants. In our multilevel analysis, we test interactions between country-specific variations in legislation on migration policies on the one hand and individual differences in political socialisation and political efficacy on the other. Our models suggest significant positive effects of exposure to a democratic regime in the country of origin and of internal efficacy on party membership of citizens of immigrant origin. Additionally, our findings highlight the significance of an inclusive national framework for immigrant integration, serving as a moderator to diminish the impact of political socialisation in less democratic countries on the decision of citizens with immigrant backgrounds to participate in political parties within their country of residence.